THE STRUCTURE OF THE FUTURE FOREIGN LANGUAGE TEACHER'S READINESS FOR PROFESSIONAL ACTIVITY IN CONDITIONS OF THE NEW UKRAINIAN SCHOOL - Oxana Rogulska (Vasyl Stefanyk Precarpathian National University, 2018)
The author's interpretation of the future foreign language teachers' readiness for professional activity at the New Ukrainian School is presented in the article. It is defined as an important integrative quality and stable personal characteristic of the future foreign language teachers, consisting of motivational and valuable, cognitive and communicative, active and practical, professional and personal, evaluative and reflexive components, is implemented in the ability to carry out effective pedagogical activity in the conditions of the New Ukrainian School and is the result of the teachers' professional training at higher educational institutions. The structure of the future foreign language teachers' readiness for professional activity in conditions of the New Ukrainian School is presented, including the following components: motivational and valuable (includes motives, needs for professional training, improvement, self-education, self-development, desire to succeed), cognitive and communicative (comprises integrated knowledge system (linguistic, psycho-pedagogical, methodical) about the essence of the teacher's work), active and practical (involves the ability to acquire and expand knowledge, organize students' activities in accordance with the goals of the educational process, taking into account modern educational technologies; ability to organize interpersonal interaction), professional and personal (involves the formation of professionally significant personality traits), evaluative and reflexive (promotes the growth of professionalism and the ability to continuous personal and professional self-improvement and growth on the basis of psychological mechanisms of self-examination, self-regulation, self-esteem and self-control); criteria: motivational, knowledgeable, operational, personal, reflexive and levels: low (reproductive), average (productive), high (professional). Key words: readiness structure, future foreign language teachers, professional activity, New Ukrainian School, components, criteria, readiness levels.